Застосування науково-методичного частотного підходу до комплексної кількісної оцінки фінансово-економічних ризиків підприємств олійно-жирової галузі України - Посохов, Ігор Михайлович; Жадан, Юлія Володимирівна (ВД "ІНЖЕК", 2019)
Метою статті є дослідження комплексної оцінки фінансового стану та застосування науково-методичного частотного підходу до комплексної кількісної оцінки фінансово-економічних ризиків підприємств олійно-жирової галузі України. Запропоновано науково-методичний підхід до комплексної кількісної оцінки фінансово-економічних ризиків підприємств олійно-жирової галузі України, що містить авторський аналітичний підхід до оцінювання ризику, який являє собою комбінацію статистичного методу й експертного аналізу; оцінку інтегрального фінансового ризику методами факторного аналізу та логіт-моделювання в динаміці на прикладі підприємств олійно-жирової галузі України. Напрямом подальших наукових досліджень є необхідність управління ризиками за допомогою розробки та використання механізму управління ризиками та побудови систем управління ризиками на підприємствах олійно-жирової галузі України.

The article is aimed at researching the comprehensive evaluation of financial condition and applying the scientific-methodological frequency approach to the comprehensive quantitative evaluation of financial-economic risks of enterprises in the oil and fat industry sector of Ukraine. The scientific-methodical approach to the comprehensive quantitative evaluation of financial-economic risks of enterprises in the oil and fat industry sector of Ukraine contains the authors’ analytical approach to risk evaluation and is a combination of a statistical method and an expert analysis. Also the evaluation of the integral financial risk using the methods of factor analysis and logit modelling in dynamics on the example of oil and fat industry sector of Ukraine is proposed. Direction of further research is the necessity for risks management through the development and use of a risks management mechanism and construction of the risk management systems at enterprises of the oil and fat industry sector of Ukraine.
Applying the Scientific-Methodical Frequency Approach to the Comprehensive Quantitative Evaluation of Financial-Economic Risks of Enterprises in the Oil and Fat Industry Sector of Ukraine
Keywords: ризик-менеджмент; ризики; система управління ризиками; risk management; risk; risk management system